"Maria que me ensina a ser mulher": religião e gênero no Santo Daime - Benedito, Camila de Pieri (2019)
This thesis is the result of the ethnography performed in the Céu do Gamarra, a religious community of Santo Daime located in the city of Baependi, in south Minas Gerais. Seeking to interpret how gender discourse develops in the community, the research explored how the "feminine" and "masculine" categories are constructed and then observed that they are conceived like essences, in opposition and complementarity, definiyng religious and daily practices of affiliates and affiliated. The construction of this discourse is related to the religious matrices that underpinned the formation and development of the Santo Daime, as well as the historical context that surrounded it. Particular emphasis is placed on devotional centrality to the Virgin of the Conception, a centrality originated from her apparition to the founder Raimundo Irineu Serra. Mary is considered the quintessence of the feminine and, therefore, an archetype to be followed by earthly women, then protagonists of the domestic universe, of sacred and natural motherhood, and the ideals of care and suffering. The thesis also observes how from this polarity also emerges a conception of sacred marriage between the "feminine" and "masculine" forces, which punctuates a heteronormative discourse that values the heterosexual, nuclear, and reproductive family. The research was developed theoretically-methodologically based on the intersection between religion and gender, covered the bibliography on the ayahuasca field, ethnographic immersion, the study of Santo Daime’s liturgical material, semi-structured interviews with leaders and affiliates of the religious community and formulation of content for the community’s website.